Readiness of cardiosurgical patients for digital rehabilitation programs. Issue 4 (29th December 2021) - Pomeshkina, S; Zvereva, T N; Krupyanko, E V; Pomeshkina, E E; Barbarash, O L
Abstract: Introduction: To date, the methods of remote rehabilitation using the mobile applications for smartphones are increasingly introduced for a particular category of cardiac patients worldwide. Such programs are of a particular relevance due to a higher accessibility for a patient which is provided by the flexibility of the patients' home training schedule and the possibility of constant communication with a cardiologist and rehabilitation therapist. Purpose: To study the readiness of the patients to participate in the remote digital cardiac rehabilitation program. Methods: 265 patients (180 (68%) men and 85 (32%) women) undergone a cardiac surgery and staying at the cardiac surgery department were examined. The mean age of the patients was 67±11.9 years. 157 (59%) patients undergone coronary artery bypass grafting (CABG), 73 (34%) patients – heart valves surgery, 13 (5%) patients – simultaneous CABG and heart valves surgery and 5 (2%) – hybrid CABG with carotid endarterectomy. Prior to the discharge from the first inpatient rehabilitation stage (10–12 days after cardiac surgery), all the patients underwent a survey. The survey was conducted using a designed questionnaire including 5 questions, the answers to which determined the patients' awareness of the necessity and the structure of postoperative remote rehabilitation using the digital technologies, as well as the willingness and the possibility to participate in these programs. Results: Analyzing the results obtained from the survey it turned out that the majority of patients (258 (97%)) believe that they need cardiac rehabilitation. However, only 86 (32%) patients answered positively to the question about their readiness to participate in remote digital rehabilitation programs. When analyzing the reasons for such a low readiness of patients to participate in remote programs it turned out that 98 (37%) patients didn't have smartphones. 10 (4%) patients despite the presence of a smartphone, refused to participate referring to their inability to use considering themselves incapable of learning it. 71 (27%) patients simply refused claiming that they don't understand the necessity for remote cardiac rehabilitation. Conclusions: Thus, only a small number of the patients (32%) are ready to participate in remote digital programs of cardiac rehabilitation. A considerable amount of the patients (37%) can't afford to participate in a remote rehabilitation program only due to the absence of the smartphone and 27% of the patients are not ready to participate in a remote cardiac rehabilitation program not understanding the importance of distance cardiac rehabilitation for them. Funding Acknowledgement: Type of funding sources: None.